How Does Bawaslu Govern Digital Spaces Through Communication and Strategies to Address 2024 Black Campaigns? - Natasya Avania Amodya, Prabowo; Syarifa Nissa, Fauziah; Zhalika, Rahmadhania; Sajida, Sajida (Universitas Merdeka Malang, 2025)
The 2024 Indonesian General Election has brought to light the central role that social media play in political narration, along with glaring instances of disinformation as well as black campaigns. These platforms are now used by political buzzers to transmit false information, which constitutes a major threat to electoral integrity. This study looks into the role of the Election Supervisory Agency (Bawaslu) in countering black campaigns and their preventive and repressive measures. The qualitative descriptive method and literature review are adopted, used to triangulate data from laws, government reports, and academic literature to test Bawaslu’s role in counteracting digital disinformation. Some preventive measures, such as public digital literacy campaigns and participatory monitoring, include initiatives like